Technology and science in the Orinoquia and the Amazon (2020)
The interdisciplinary collection Studies of the Orinoquia and the Amazon seeks to generate knowledge, encourage academic discussion, and assume alternative solutions to regional problems in the region. If the Orinoquia and the Amazon are special territories due to their historical abandonment and they constitute a unique land, they must have a special treatment that facilitates their development and promotes access to scientific knowledge and goods produced in the developed world with respect for populations ancestral and regional cultures. In this first volume are works related to veterinary medicine and health research in this region. The themes are varied and must be assumed from a theoretical, methodological, and procedural opening to reach an understanding of the phenomenon in its dimensions and its contexts.